Development of Recent Humanoid Robot - Kim, Chang-Hyun; Choi, Tae-Yong; Lee, Ju-Jang (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.